The Effect of Imagery Training in Increasing the Confidence - Putri Cicilia Kristina; Endie Riyoko; Perabunita Perabunita; Daryono Daryono (Universitas PGRI Palembang, 2022)
This study aims to determine the effect of mental imagery training on increasing Athletes' Confidence in facing the competition at the Futsal Athletes of the Musi Banyuasin Club, South Sumatra. This type of research is an experiment with the design of